2020
DOI: 10.14715/cmb/2020.66.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, saponins and alkaloids on cancer progression: emphasis on p53 expression and telomere length

Abstract: Telomere length is correlated with cell proliferation, and cancer cells are characterized by an uncontrolled cell cycle. Being apoptosis one of the checks and balances incorporated into cells cycle, due to its characteristics, cancer cells are able to overcome this process. In particular, the tumour suppressor protein p53 loss or inactivation can lead to activation of telomerase enzyme, which can make cells unable to detect DNA damages that spurs apoptosis. Some bioactive compounds, in particular phenolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The main concept of the report was that phenolic compounds, saponins, and alkaloids presumably interfere with cancer progression by stimulating p53 expression with subsequent pro-apoptotic onset. Additionally, the anti-apoptotic activity was suppressed and telomerase activity was protected [ 95 ]. In our recent study, we demonstrated that Ganoderma lucidum (GLC) extract induced oxidative DNA damage selectively in CRC cell lines (HCT116, HT29, and HCT116 p53-/- ), whereas it protected non-malignant cells from the accumulation of reactive oxygen species.…”
Section: Studies On the Interactions Of Dna Repair Telomere Homeomentioning
confidence: 99%
“…The main concept of the report was that phenolic compounds, saponins, and alkaloids presumably interfere with cancer progression by stimulating p53 expression with subsequent pro-apoptotic onset. Additionally, the anti-apoptotic activity was suppressed and telomerase activity was protected [ 95 ]. In our recent study, we demonstrated that Ganoderma lucidum (GLC) extract induced oxidative DNA damage selectively in CRC cell lines (HCT116, HT29, and HCT116 p53-/- ), whereas it protected non-malignant cells from the accumulation of reactive oxygen species.…”
Section: Studies On the Interactions Of Dna Repair Telomere Homeomentioning
confidence: 99%
“…Cell cycle disorder is one of the characteristics of cancer, which can result in unbounded cell proliferation and cancer development [37,38]. The disorder of cell proliferation and metastasis is an important reason for the occurrence and development of tumors [39].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle disorder is one of the characteristics of cancer, which can result in unbounded cell proliferation and cancer development [ 37 , 38 ]. The disorder of cell proliferation and metastasis is an important reason for the occurrence and development of tumors [ 39 ]. Overall, the GSEA analysis demonstrated the preceding speculation that the POP1 overexpression appeared to be more likely associated with the enhancement of BC cell growth and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…About 41.08% of students were aware that pyrrolizidine alkaloids present in various edible plants have been shown to be mutagenic in Salmonella strains and carcinogenic in rodents. Petasitenine and senkirkine are responsible for the carcinogenicity of two kinds of coltsfoot, P.japonicus Maxim and T.farfara L., respectively, inducing liver tumors in rats [31]. The commonly eaten cultivated mushroom, Agaricus bisporus, contains a hydrazine compound, agaritine (β-N-[γ-L(+)-glutamyl]-4-hydroxymethyl phenyl hydrazine), and its decomposition products.…”
Section: Discussionmentioning
confidence: 99%